Falling [large type] - Green, Jane, 1968- (Thorndike Press, A part of Gale, Cengage Learning, 2016)
"Eight years ago, Emma Montague left behind the strict confines--and rather dull boyfriend--of her upper-crust English life and moved to New York City, where she immediately found success in finance. But her soulless, cutthroat, all-consuming job was another life she didn't want. Answering an ad on Craigslist, Emma finds a tiny beach cottage in the small town of Westport, Connecticut. It needs work--lots of work. But it's the perfect project to satisfy Emma's passion for interior design and gardening, if her new landlord, Dominic, is agreeable to the small changes she yearns to make. To Emma, Dominic himself is somewhat of a fixer-upper. A local handyman with a six-year-old son, he's a world away from the men she should be interested in, but he's comfortable in his own skin, confident, quiet, and kind. And slowly, over a shared garden, time spent with his son, and late-night conversations, Emma finds herself falling for Dominic ... From friends to lovers happens as naturally as the changing seasons. But setting down roots doesn't come easily when two lives as different as their own merge into one. And Emma will realize that the seeds of happiness must be nurtured and cherished to grow into something strong enough to shelter all their hopes and dreams.."--